LOOKING INTO MY BACKYARD: SHIFTS IN PROFESSIONAL IDENTITY - Teuku Zulfikar (AT-TA'LIM, 2012)
Professional development is a long-life journey and rewarding in an academia. Teachers are required to improve their competences. They do not only enhance their subject matters but also upgrade their pedagogical knowledge. Professional development can be conducted through many ways. It could be done through formal education, informal training or self-reflection. This is reflexivity on an English teacher’s professional journey. It scrutinizes phases of language learning and teaching awareness. The article starts with my first contact with English and then goes on to learning-teaching experience in the later phases. The reflection on these experiences shapes my teaching identity and improves teaching competence.